Reading Nepal Through Gadi Wolfsfeld: The Power Nexus Between Politics and Media - Paudel, Sunil; Khan, Nilima Chandani (Madhesh Journal of Interdisciplinary Research, 2026)
This review article explores Gadi Wolfsfeld’s five principles of political communication in light of the power dynamics of politics and the media in Nepal. It examines the various aspects of editorial autonomy, press freedom and public discourse that are influenced by political power, media visibility, ownership and media advertising policies of the state, legal uncertainty, journalistic routines and digital platforms. The study uses qualitative, descriptive design, analysis, integration, secondary sources related to scholarly literature, policy documents, legal documents, press freedom documents, institutional documents and press documents issued by credible media as source documents. The study reveals that the media in Nepal has passed from the direct control of the State in Panchayat era to plural media in 1990 but still politically influenced. While press freedom and freedom of expression are guaranteed under the constitution, the vagueness of the laws, the regulatory instability, economic dependence and political patronage still have an impact on the status of media independence. It is also found that ownership, State advertising, elite source dependence influence the political communication in Nepal, conflict-centred reporting and Kathmandu-centric news routines. While these digital platforms have facilitated the empowerment of political actors beyond merely offering new modes of communication, they have also created new problems, including that of misinformation, online harassment, algorithmic control, and state regulation. The article concludes that Nepal’s media-politics relationship is not wholly free nor it is wholly at the control of the media. Instead, it works in an arena of negotiated political, economic, legal, professional and technical power.